Alveolar Overdistension as a Cause of Lung Injury: Differences among Three Animal Species - Manuel García-Delgado; Inés Navarrete-Sánchez; Virginia Chamorro-Marín; Juan Carlos Díaz-Monrové; Javier Esquivias; Enrique Fernández-Mondéjar (The Scientific World Journal)
This study analyses characteristics of lung injuries produced by alveolar overdistension in three animal species. Mechanical ventilation at normal tidal volume (10 mL/Kg) and high tidal volume (50 mL/Kg) was applied for 30 min in each species. Data were gathered on wet/dry weight ratio, histological score, and area of alveolar collapse. Five out of six rabbits with high tidal volume developed tension pneumothorax, and the rabbit results were therefore not included in the histological analysis. Lungs from the pigs and rats showed minimal histological lesions. Pigs ventilated with high tidal volume had significantly greater oedema, higher neutrophil infiltration, and higher percentage area of alveolar collapse than rats ventilated with high tidal volume. We conclude that rabbits are not an appropriate species for in vivo studies of alveolar overdistension due to their fragility. Although some histological lesions are observed in pigs and rats, the lesions do not appear to be relevant.